ADAPTED TO THE ECOLOGY OF UZBEKISTAN PLANTS AND ANIMALS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article provides detailed information about ephemerals, ephemeroids, plants adapted to the desert (plain), gypsum desert, saline soils, and animal species found in shallow waters, forests, rivers, and mountain plains.